Extending the Spiral of Silence: Partisan Media, Perceived Support, and Sharing Opinions Online. Issue 3 (3rd July 2017) - Wang, Meredith Y.; Hmielowski, Jay D.; Hutchens, Myiah J.; Beam, Michael A.
ABSTRACT: In this paper, we apply the spiral of silence theory to the study of partisan media and political participation. Our results show consuming supportive partisan news outlets is associated with perceiving that other people share one's opinions. In addition, levels of perceived support are associated with the likelihood of sharing opinions in online contexts. Moreover, our result shows that the relationship between perceived support and sharing opinions varies by the individual difference variable of conflict avoidance. To test our model, we use data collected right before the 2014 midterm election in the United States.